Therapeutic Interventions for Frail Elderly Patients: Part I. Published Randomized Trials - Bibas, Lior; Levi, Michael; Bendayan, Melissa; Mullie, Louis; Forman, Daniel E.; Afilalo, Jonathan (Progress in cardiovascular diseases, 2014)
The body of literature for frailty as a prognostic marker continues to grow, yet the evidence for frailty as a therapeutic target is less well defined. In the setting of cardiovascular disease, the prevalence of frailty is elevated and its impact on mortality and major morbidity is substantial. Therapeutic interventions aimed at improving frailty may impart gains in functional status and survival. Randomized clinical trials that tested one or more therapeutic interventions in a population of frail older adults were reviewed. The interventions studied were exercise training in 13 trials, nutritional supplementation in 4 trials, combined exercise plus nutritional supplementation in 7 trials, pharmaceutical agents in 8 trials, multi-dimensional programs in 5 trials, and home-based services in 1 trial. The main findings of these trials are explored along with a discussion of their relative merits and limitations.